1994
DOI: 10.1111/j.1469-7998.1994.tb01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐related mating success in the shore crab Carcinus maenas (Crustacea: Brachyura)

Abstract: The relationship between the size of a given mating male Carcinus maenas (L.) (Brachyura, Portunidae) and the size of the female with which it was paired was studied for 1248 pairs of crabs collected from the shore In 764 of these pairs the female was in pre‐moult and so the pair were in pre‐copula. In the remaining 484 pairs the female had already moulted and the pairs were in copula. There were significant correlations between the sizes of the males and females in both pre‐copula and copula pairs. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Evidence that male sexual competition was relaxed in 1995-96 also comes from the lower ratio of pubescent to nulliparous and primiparous females ( Table 1 ) . This suggests that the duration of precopulatory guarding by males was reduced (see Reid et al 1994), as predicted under circumstances of greater female availability (Grafen & Ridley 1983). (3) Finally, a laboratory study has shown that males fight for pubescent and nulliparous females and that there is a size advantage in sexual competition (Sainte-Mane et al 1997); this is also suggested by casual observations of interactions between males and females in the field (Sainte-Mane & Hazel 1992).…”
Section: Genetic Evidence For Multiple Mating Of Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that male sexual competition was relaxed in 1995-96 also comes from the lower ratio of pubescent to nulliparous and primiparous females ( Table 1 ) . This suggests that the duration of precopulatory guarding by males was reduced (see Reid et al 1994), as predicted under circumstances of greater female availability (Grafen & Ridley 1983). (3) Finally, a laboratory study has shown that males fight for pubescent and nulliparous females and that there is a size advantage in sexual competition (Sainte-Mane et al 1997); this is also suggested by casual observations of interactions between males and females in the field (Sainte-Mane & Hazel 1992).…”
Section: Genetic Evidence For Multiple Mating Of Femalesmentioning
confidence: 99%
“…Reid et al 1994). Assuming that males choose their mates, the weakness of size correlations in some species has been attributed to the fact that female body size is a poor predictor of fecundity (Jivoff 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Body size can also strongly determine the ability to attract mates (e.g. Salmon, 1983;Sekkelsten, 1988;Reid et al, 1994;van der Meeren, 1994) and the level of reproductive output (Hines, 1982). The degree to which individual performance is handicapped will vary with the type and number of missing or regenerating limbs (Smith & Hines 1991a, Smith 1992 and with the length of time the animal must function without its services.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in diet composition between genders and maturity stages have also been found in other shrimps, Plesionika heterocarpus and Plesionika martia (Fanelli and Cartes 2008). Aggregative behaviour within genders has also been related to other causes, such as the need to look for appropriate habitat for moulting (Reid et al 1994, Sampedro and González-Gurriarán 2004 or for hatching (i.e. females look for suitable sites to improve dispersal and survival of recently hatched larvae) (Hicks 1985, Zeng and Naylor 1997, Carr et al 2004).…”
Section: Size Dimorphism and Sex Ratiomentioning
confidence: 99%